Peran Pelaku UMKM Usaha Besi Bekas Dan Implikasinya Terhadap Ketahanan Ekonomi Keluarga (Studi di Kota Balikpapan, Kalimantan Timur) - Wibisono, Gunawan (Universitas Gadjah Mada, 2024)
Population growth in Balikpapan City is very high, Based on data from BPS Kaltim, the population growth rate from 2020 to 2022 is 1.26% and Balikpapan City has been designated as a buffer city for the capital of the archipelago, this is currently one of the national development priorities. There are many immigrants both from Kalimantan Island and from outside the island, which reduces the opportunities for Balikpapan City residents to earn income and increase family economic resilience. The scrap metal business as an Micro, Small and Medium Enterprise (MSME) is an opportunity to expand employment for the people of Balikpapan City, with the potential availability of scrap iron in Balikpapan City and also driven by the relatively high national demand for iron raw materials. Therefore, this research aims to analyze the role of scrap metal business actors as MSMEs and its implications for the economic resilience of families in Balikpapan City.This research uses a descriptive qualitative approach to explain the actual situation that is occurring and answer problems using scientific procedures. The research location is in Balikpapan City, with the objects studied being scrap metal business actors from various categories. Informants were selected using purposive sampling techniques and strengthened by snowball sampling. Data was analyzed qualitatively by data reduction, data presentation, drawing conclusions.The results of data analysis show that the role of scrap metal business actors in Balikpapan City between the three categories which include prospectors, collectors and scrap metal senders has a related relationship in terms of meeting scrap metal needs and fulfilling business capital. In terms of implications for family economic resilience, it was found that the economic resilience of prospectors for scrap metal was still weak because only four of the seven indicators of family economic resilience were fulfilled. Meanwhile, scrap metal collectors and shippers have strong family economic resilience, because they have fulfilled six of the seven indicators of family economic resilience.